Targeting of PDGF-C/NRP-1 autocrine loop as a new strategy for counteracting the invasiveness of melanoma resistant to braf inhibitors - Federica Ruffini; Claudia Ceci; Maria Grazia Atzori; Simona Caporali; Lauretta Levati; Laura Bonmassar; Gian Carlo Antonini Cappellini; Stefania D'Atri; Grazia Graziani; Pedro Miguel Lacal (Elsevier, 2023)
Melanoma resistance to BRAF inhibitors (BRAFi) is often accompanied by a switch from a proliferative to an invasive phenotype. Therefore, the identification of signaling molecules involved in the development of metastatic properties by resistant melanoma cells is of primary importance. We have previously demonstrated that activation of neuropilin-1 (NRP-1) by platelet-derived growth factor (PDGF)-C confers melanoma cells with an invasive behavior similar to that of BRAFi resistant tumors. Aims of the present study were to evaluate the role of PDGF-C/NRP-1 autocrine loop in the acquisition of an invasive and BRAFi-resistant phenotype by melanoma cells and the effect of its inhibition on drug resistance and extracellular matrix (ECM) invasion. Furthermore, we investigated whether PDGF-C serum levels were differentially modulated by drug treatment in metastatic melanoma patients responsive or refractory to BRAFi as single agents or in combination with MEK inhibitors (MEKi). The results indicated that human melanoma cells resistant to BRAFi express higher levels of PDGF-C and NRP-1 as compared to their susceptible counterparts. Overexpression occurs early during development of drug resistance and contributes to the invasive properties of resistant cells. Accordingly, silencing of NRP-1 or PDGF-C reduces tumor cell invasiveness. Analysis of PDGF-C in the serum collected from patients treated with BRAFi or BRAFi+MEKi, showed that in responders PDGF-C levels decrease after treatment and raise again at tumor progression. Conversely, in non-responders treatment does not affect PDGF-C serum levels. Thus, blockade of NRP-1 activation by PDGF-C might represent a new therapeutic approach to counteract the invasiveness of BRAFi-resistant melanoma.